2021
DOI: 10.3390/s21051786
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Patients with Sarcopenia Using Gait Parameters Based on Inertial Sensors

Abstract: Sarcopenia can cause various senile diseases and is a major factor associated with the quality of life in old age. To diagnose, assess, and monitor muscle loss in daily life, 10 sarcopenia and 10 normal subjects were selected using lean mass index and grip strength, and their gait signals obtained from inertial sensor-based gait devices were analyzed. Given that the inertial sensor can measure the acceleration and angular velocity, it is highly useful in the kinematic analysis of walking. This study detected s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 47 publications
1
36
0
2
Order By: Relevance
“…Thus, they are useful for implementing strategies to reduce the risk of falls which represents a major public health problem [50]. Recent reports suggest that IMUs, besides being useful in evaluating and to monitoring gait alterations in patients with neurodegenerative diseases such as Parkinson's disease [51][52][53], are useful for; patients with osteoarthritis [54], with benign paroxysmal positional vertigo, the most common peripheral vestibular disorder, leading to balance difficulties and increased fall risks [55] and walking disturbances in sarcopenic patients [56], they are also useful for gait event detection and analysis of gait alterations in patients with diabetes secondary to DPN [23,24,[27][28][29]31]. In spatiotemporal gait parameters recorded using a wearable sensor in patients with DPN, Kang et al showed that gait initiation steps and dynamic balance may be more sensitive than gait speed for detecting gait deterioration due to DPN [23], and Najafi et al demonstrated that gait alteration in patients with DPN is most pronounced while walking barefoot over longer distances [31].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they are useful for implementing strategies to reduce the risk of falls which represents a major public health problem [50]. Recent reports suggest that IMUs, besides being useful in evaluating and to monitoring gait alterations in patients with neurodegenerative diseases such as Parkinson's disease [51][52][53], are useful for; patients with osteoarthritis [54], with benign paroxysmal positional vertigo, the most common peripheral vestibular disorder, leading to balance difficulties and increased fall risks [55] and walking disturbances in sarcopenic patients [56], they are also useful for gait event detection and analysis of gait alterations in patients with diabetes secondary to DPN [23,24,[27][28][29]31]. In spatiotemporal gait parameters recorded using a wearable sensor in patients with DPN, Kang et al showed that gait initiation steps and dynamic balance may be more sensitive than gait speed for detecting gait deterioration due to DPN [23], and Najafi et al demonstrated that gait alteration in patients with DPN is most pronounced while walking barefoot over longer distances [31].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al developed a sarcopenia classification model by performing SVM algorithm from data collected by 2 IMU during walking (Accuracy: 95%). 30 The sarcopenia classification model showed a higher performance than that of the sarcopenia classification model developed in this study. However, the reason for such performance difference is that more IMUs were used for measuring physical activity.…”
Section: Discussionmentioning
confidence: 55%
“…Lastly, a very recent article [14] aimed at identifying and elaborating parameters from gait signals produced by the sensors in order to develop a screening and classification method for sarcopenia. In the study were used specific parameters that they interpreted through an artificial intelligence (AI) model called SHAP (Shapley Additive Explanations).…”
Section: Accelerometer and Actigraph Technology In Wearable Inertial Sensorsmentioning
confidence: 99%
“…In the study were used specific parameters that they interpreted through an artificial intelligence (AI) model called SHAP (Shapley Additive Explanations). The features obtained through the inertial signals were not exhaustive; for this reason, further data and greater cohorts, respectively, with additional clinical evaluations should be collected and studied [14].…”
Section: Accelerometer and Actigraph Technology In Wearable Inertial Sensorsmentioning
confidence: 99%